The impact of borrower-based instruments on household vulnerability in Germany - Nataliya Barasinska; Johannes Ludwig; Edgar Vogel (Deutsche Bundesbank, 2021)
Excessive household borrowing has been identified as an important determinant of financial crises. Borrower-based macroprudential instruments have been proposed as a possible remedy. In Germany, two instruments have been available to macroprudential supervisors since 2017: a cap on the loan-to-value (LTV) ratio and an amortization requirement, but none of them has been activated so far. Therefore, this paper presents a simulation tool that allows the impact of activating of borrower-based instruments to be evaluated ex ante. The simulation is based on microdata from the German Panel on Household Finances (PHF) and is at the same time calibrated to match aggregate developments in the residential real estate market. This micro-macro consistent simulation approach can be used to detect vulnerabilities in household balance sheets and perform an ex ante analysis of the activation and calibration of borrower-based macroprudential instruments. An illustrative example of a hypothetical activation shows that the introduction of a cap on the loan-to-value (LTV) ratio of new mortgage loans in Germany could improve important indicators of household vulnerability.
Keywords: D14; G17; G21; G28; R21; 330; Household finance; mortgages; macroprudential policy; borrower-based instruments; financial stability